Comparison Between Varicocelectomy and Varicocele Sclerotherapy: Results of a Single-Center Observational Study - Rossella Cannarella; Vittorio Cannarella; Rosario Randazzo; Andrea Crafa; Michele Compagnone; Laura M. Mongioì; Rosita A. Condorelli; Vincenzo Bagnara; Sandro La Vignera; Aldo E. Calogero (Life)
Affecting up to 15% of men worldwide, varicocele has been recognized as a cause of infertility, and its repair is associated with an improvement in conventional and bio-functional sperm parameters. Various surgical and radiological techniques exist for varicocele repair. However, it is unclear which technique is associated with greater clinical efficacy. This retrospective, single-center study aimed to compare the effectiveness of surgical treatment (Ivanissevich technique) versus radiological treatment (sclerotherapy) in a cohort of 94 patients with varicocele. After varicocele repair, a significant increase in sperm concentration was observed only in the group of patients treated with sclerotherapy. A significant reduction in the percentage of patients with oligozoospermia was found in the group of patients treated surgically. Patients undergoing surgical varicocelectomy had increased serum luteinizing hormone (LH) levels, decreased spermatid concentration, and increased percentage of spermatozoa in late apoptosis, probably as a result of surgical traumatism. In conclusion, the results of this study did not show a clear benefit of one technique over the other and confirm the findings of the current literature. However, it remains one of the few on the topic that also considers sperm bio-functional parameters among its outcomes and opens the research up to new considerations on the bio-functional sperm parameters.